Mothers at work effects on children's well-being - Hoffman, Lois Norma Wladis 1929- (Cambridge studies in social and emotional development, 1999)
This important 1999 volume examines the effects of the mother's employment on family life and children's well-being. It starts with a thorough review of previous research on this topic and then reports the results of a study designed to answer the key questions that emerge. The study focuses on 448 families, with an elementary school child, living in an industrialized city in the Midwest. They include both one-parent and two-parent families, African Americans and Whites, and a broad range of economic circumstances. Extensive data have been obtained from mothers, fathers, children, teachers, classroom peers, and school records. The analysis reported reveals how the mother's employment status affects the father's role, the mother's sense of well-being, and childrearing patterns and how these, in turn, affect the child. The book provides an intimate picture of urban life and how families cope with mothers' employment